Designing an overview Theory of Change for a multi-component support community for people affected by rare dementia - Sullivan, Mary Pat; Camic, Paul M.; Harding, Emma; Stott, Joshua; Windle, Gill; Davies-Abbott, Ian; Crutch, Sebastian J. (Frontiers in Dementia, 2025)
IntroductionThere is growing awareness of people living with diverse dementia syndromes, many of whom are younger in age, with distinct support needs. Planning for increasing numbers of people living with dementia and subsequent models of support has largely overlooked this population. To address this gap, the aim was to design a Theory of Change for multi-component rare dementia support.MethodsIntervention development frameworks underpinned the construction of a Theory of Change informed by research evidence on rare dementia support and an iterative consultation process with people with lived experience, researchers, educators and health and social care practitioners.ResultsThe Theory of Change illustrates pathways to activities for continuous and tailored support solutions, education and knowledge production. Characteristic features include relationship, connection and continuity for people with lived experience, training and networking for professionals, and relational support with a commitment to ongoing learning for the rare dementia support team.ConclusionThe Theory of Change is positioned to flexibly support people affected by rare dementia, strengthen capacity within all sectors, improve service quality whilst maintaining a commitment to knowledge production and mobilization.